Electoral support for left wing populist parties in Europe: addressing the globalization cleavage. Issue 5 (20th October 2018) - Santana, Andrés; Rama, José
ABSTRACT: Drawing on the European Electoral Study (EES) for the 2014 European Parliamentary elections, we analyse the electoral competition between left wing populist parties and their non-populist counterparts in the nine European countries where this type of competition has occurred. By using the EES, we hold constant the electoral level and the electoral system, the timing of the elections and the question wording. To our knowledge, this is one of the broadest comparative analyses of European left-wing populist parties so far. The focus on the competition between leftist parties draws attention to the key question of the vulnerabilities of the non-populist left vis à vis their populist competitors. We test a battery of bivariate clustered logistic models and find that the losers of globalization theories help account for left wing populist parties' support. However, the sociodemographic profile of these supporters does not fit the mainstream view on who these losers are. Moreover, we obtain strong support for the globalization cleavage theories: citizens who hold critical attitudes towards the EU and who perceive immigration as a threat to their 'way of life' are more prone to support left wing populist parties than non-populist left parties. These findings apply both to the entire sample of countries and to each one of them individually.